2014
DOI: 10.15835/nbha.42.2.9740
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Biofuel Crop Production in Romania over the Last Decades - Possible Impacts on Environment, Greenhouse Gas Emissions and Land Use

Abstract: The interest in biofuels is growing globally and the demand for bioenergy throughout the European Union will expand considerably in the following years. Numerous studies have shown that energy resulted from green plants has much to offer, as it is renewable and largely carbon-neutral compared with fossil fuel combustion. However, this is an increasingly controversial issue due to its strong impact on economy, environment and land use. Romania is one of the European Union Member States with a large biofuel prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…5) To ensure new opportunities up to the limits of the market for biofuels. Romanian agriculture has major potential to develop the growing of crops for the production of biofuels (Stan et al 2014), with this therefore capable of setting a new strategic direction for further investment. The European Commission promotes biofuel production, but with caution, as key operators in farming may prove more interested in developing these kinds of industrial crops, as opposed to food.…”
Section: Challenges For Romanian Agriculturementioning
confidence: 99%
“…5) To ensure new opportunities up to the limits of the market for biofuels. Romanian agriculture has major potential to develop the growing of crops for the production of biofuels (Stan et al 2014), with this therefore capable of setting a new strategic direction for further investment. The European Commission promotes biofuel production, but with caution, as key operators in farming may prove more interested in developing these kinds of industrial crops, as opposed to food.…”
Section: Challenges For Romanian Agriculturementioning
confidence: 99%
“…Evidence showed that the damage of transport emissions to the environment and the worsening of living conditions due to population growth and limitless resource consumption needed urgent attention. With reference to exhaust gases emitted by urban transportation, this encompasses a wide range of effects on human health [10][11][12]. Literature suggests that urban traffic is responsible for 40% of CO2 emissions and 70% of the emission of other pollutants arising from transport [13].…”
Section: A Short Presentation Of the Plant And Productsmentioning
confidence: 99%